ANALISA RANGKA LOAD-FRAME DARI ALAT TRIAXIAL DIGITAL 50 KN - Putera, Eka; Saputra, Hendri Maja; Ruchimat, Ruchimat (JURNAL TURBULEN, 2018)
ABSTRACT An analysis of the strength of the material on the framework of the digital triaxial apparatus to increase the maximum working capability to 50 kN has been performed. A digital triaxial device is a test machine used to determine the properties of a soil sample. Analysis of the framework of this tool is needed to see the character of the material used so as to obtain maximum performance to support the performance of the digital triaxial device. The frame in question consists of a bottom base, two poles, and a beam rod positioned at the top of the pole. The analysis performed using 3D Solidworks software utilizes structural analysis features. Pressures of 50 kN are given in a vertical direction so as to press the midpoint of the bottom base and the beam rod, both of which are attached to the pole using a nut as anchoring. The analysis result shows that Stress Von Mises maximum vallue that works on parts is 1.664,7 kgf/cm2.